Intravenous lipid emulsion therapy in 20 cats accidentally overdosed with ivermectin. (23rd September 2015) - Jourdan, Geraldine; Boyer, Guillaume; Raymond‐Letron, Isabelle; Bouhsira, Emilie; Bedel, Benjamin; Verwaerde, Patrick
Abstract Objective To describe the outcome of 20 cats treated with intravenous lipid emulsion (IVLE) after an accidental parenteral ivermectin overdose. Case Series Summary Twenty adult cats presented after receiving a 4 mg/kg accidental subcutaneous overdose of ivermectin. After admission, two IVLE treatments were initiated in asymptomatic cats: a single bolus (1.5 mL/kg; n = 16) versus a bolus followed by a 30‐minute constant rate infusion (0.25 mL/kg/min; n = 4). Six out of the 16 cats that received only the single bolus developed clinical signs of ivermectin intoxication. Based on the severity of the clinical signs and their duration (approximately 48 hours), these 6 cats were retrospectively considered either moderately (n = 3) or severely (n = 3) intoxicated by ivermectin. Cats with a low body condition score (BCS) had more severe signs of ivermectin toxicity. Additional IVLE was administered until clinical resolution was complete. Median (min to max) cumulative dose of IVLE per cat was 4.5 (3.0–4.5) mL/kg for 36 (12–36) hours and 19.5 (7.5–37.5) mL/kg for 96 (72–168) hours for moderately and severely intoxicated cats, respectively. New or Unique Information Provided Our series describes the treatment of accidental ivermectin parenteral overdose in 20 cats with early initiation of IVLE therapy. An early bolus followed by a 30‐minute constant rate infusion of IVLE appeared to mitigate the signs of ivermectin toxicosis in cats compared to a single treatment bolus. Our observations also suggest that cats with a low BCS given only a bolus of IVLE treatment were more likely to develop signs of ivermectin intoxication and require a greater amount of IVLE for the resolution of clinical signs. Based on our observations, BCS appears to influence the severity of ivermectin toxicity with a low BCS being associated with more severe signs of ivermectin toxicity.